2013
DOI: 10.1002/cam4.68
|View full text |Cite
|
Sign up to set email alerts
|

Slug increases sensitivity to tubulin‐binding agents via the downregulation of βIII and βIVa‐tubulin in lung cancer cells

Abstract: Transcription factor Slug/SNAI2 (snail homolog 2) plays a key role in the induction of the epithelial mesenchymal transition in cancer cells; however, whether the overexpression of Slug mediates the malignant phenotype and alters drug sensitivity in lung cancer cells remains largely unclear. We investigated Slug focusing on its biological function and involvement in drug sensitivity in lung cancer cells. Stable Slug transfectants showed typical morphological changes compared with control cells. Slug overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
3
16
0
1
Order By: Relevance
“…On the other hand, it is reported that Slug increases sensitivity to tubulin-binding agents in lung cancer cells. Thus, the role of Slug in chemoresistance might depend on the type of drug [31].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, it is reported that Slug increases sensitivity to tubulin-binding agents in lung cancer cells. Thus, the role of Slug in chemoresistance might depend on the type of drug [31].…”
Section: Discussionmentioning
confidence: 98%
“…Changes of TUBB3 and TUBB4B levels have been studied with respect to the regulation of cancer progression [6]. Understanding of the well-characterized mechanism of decreased sensitivity of cancer cells to tubulin-binding agents (TBAs) like vinca alkaloids and taxanes, comes from the analysis of TUBB3 and TUBB4B level regulation in non-small cell lung cancer and prostate cancer development [12,13,14,15,16]. Additionally, TUBB3, TUBB4B, and TUBB6 downregulation were observed in taxane-resistant breast cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to our results, the in vivo study by also demonstrated that the proliferation effect of ART1 was more obvious under cisplatin stimulation compared with no stimulation. Similarly, several studies illustrated that TUBB3, which can regulate the cell sensitivity to tubulin-binding agents such as VCR, plays important roles in the drug-induced cell apoptosis and efficiency of chemotherapy in pancreatic cancer, breast cancer, and lung cancer (Stengel et al 2010;Tamura et al 2013;Li et al 2014;McCarroll et al 2015). Therefore, we performed Western blot to test the TUBB3 expression level and found it can be positively regulated by ART1, indicating that TUBB3 may participate in the ART1-enhanced VCR resistance of glioma cells.…”
Section: Discussionmentioning
confidence: 85%